Peculiar Features of Burning Alternative Motor Fuels - M. Assad; O. G. Penyazkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Some peculiar features of air-hydrogen mixture combustion process in a modeling combustion chamber are given in the paper. Dependences of burning duration of various fuel types on initial pressure have been obtained. The paper considers dynamics of changes in pressure and ignition rate of some fuel types in the combustion chamber.